2021
DOI: 10.1111/resp.14116
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with advanced idiopathic pulmonary fibrosis treated with nintedanib or pirfenidone in a real‐world multicentre cohort

Abstract: Background and objective: Antifibrotic therapy with nintedanib or pirfenidone slows disease progression and reduces mortality in patients with idiopathic pulmonary fibrosis (IPF). However, patients with advanced IPF, as defined by forced vital capacity (FVC) < 50% and/or diffusion capacity for carbon monoxide (DLCO) < 30% of predicted, have not been included in randomized trials, and the outcomes of such patients who initiate treatment are not well understood. We determined lung function, disease progression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…PFTs from 577 adult individuals, aged 18-85 years, all of Caucasian ethnicity, were included in the study. The PFTs were obtained from subjects who had participated in recent clinical studies (15,(29)(30)(31)(32)(33) and comprised four different groups (long-term survivors of severe blood disorders, n = 229, pulmonary brosis, n = 148, lung transplantation, n = 88, and healthy, never-smoking controls, n = 112). The clinical studies had all been approved by the hospital's Data Protection O cer and the Regional Committee for Medical and Health Research Ethics.…”
Section: Design and Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…PFTs from 577 adult individuals, aged 18-85 years, all of Caucasian ethnicity, were included in the study. The PFTs were obtained from subjects who had participated in recent clinical studies (15,(29)(30)(31)(32)(33) and comprised four different groups (long-term survivors of severe blood disorders, n = 229, pulmonary brosis, n = 148, lung transplantation, n = 88, and healthy, never-smoking controls, n = 112). The clinical studies had all been approved by the hospital's Data Protection O cer and the Regional Committee for Medical and Health Research Ethics.…”
Section: Design and Study Populationmentioning
confidence: 99%
“…Consistent interpretation of PFTs across centers is important to ensure equity of care. Percent predicted values for PFTs are often included in criteria for diagnosis and severity of pulmonary diseases, in guidelines for treatment, inclusion criteria for clinical studies, and legal assessment for health bene ts (12)(13)(14)(15)(16)(17)(18)(19). Further, since the lower limit of normal (LLN) will vary with different sets of reference equations, the ability to discriminate health from disease may be affected.…”
Section: Introductionmentioning
confidence: 99%
“…Durheim et al examined disease progression and mortality following initiation of antifibrotics in patients with advanced IPF (n = 66) compared to mild to moderate IPF (n = 436). 80 They identified that patients with advanced IPF did not demonstrate more rapid lung function decline but did have higher mortality, indicating that prospective studies in high-risk groups are required. Glaspole et al assessed the efficacy of nintedanib in patients with IPF who were elderly and had multiple comorbidities from pooled data of five separate clinic trials.…”
Section: Antifibrotics In Fibrosing Ildsmentioning
confidence: 99%
“…Whether antifibrotics should be commenced in advanced disease or in older patients were also addressed. Durheim et al examined disease progression and mortality following initiation of antifibrotics in patients with advanced IPF ( n = 66) compared to mild to moderate IPF ( n = 436) 80 . They identified that patients with advanced IPF did not demonstrate more rapid lung function decline but did have higher mortality, indicating that prospective studies in high‐risk groups are required.…”
Section: Therapeutic Advances In Ildmentioning
confidence: 99%
“…Currently, nintedanib and pirfenidone are the only Food and Drug Administration (FDA)-approved drugs for the treatment of pulmonary fibrosis, which only serve to slow the progression of pulmonary fibrosis 7 . Investigating new promising molecular pathways involved in fibrogenic responses is urgently needed, and Rev-erbα has become a promising candidate 8,9 .…”
mentioning
confidence: 99%